A SCOPING REVIEW ON THE VIABILITY OF BLOCKCHAIN SOLUTION FOR LAND REGISTRY SYSTEMS IN NIGERIA - Yahya, Suleiman; Bello, Larai Muhammad; Salihu, Ibrahim Anka (FUDMA Journal of Sciences, 2026)
Inefficiency and fraud are some of the issues afflicting the land administration system in developing countries such as Nigeria. Though highly beneficial, adopting blockchain technology comes with a high degree of complexity and risks. This scoping review systematically attempts to outline the existing literature to determine the major factors influencing the feasibility of blockchain in land registry system (2022-2025). This scoping review summarizes the specified benefits, challenges, and core focus of current research through the thematic analysis of 20 modern scholarly works. The results show that there is overwhelming agreement about the possible benefits of the technology including security and transparency. However, there is also substantial and ongoing disagreement about issues of technical readiness, legislative and regulatory gaps, and socio-political issues. The scoping review concludes with a predominant research gap: A lack of a systematic evidence-based framework for stakeholders to systematically assess these viability factors. Accordingly, this study outlines the existing research and clarifies a definitive research direction to derive an implementable decision-support tool for the public sector.